Lifesaving Treatment of Aortic Valve Staphylococcus aureus Endocarditis: Daptomycin and Early Surgical Therapy - Yozgat, Can Yilmaz; Uzuner, Selcuk; Ay, Yasin; Temur, Hafize Otcu; Bursal Duramaz, Burcu; Turel, Ozden; Calim, Muhittin; Buyukpinarbasili, Nur; Yozgat, Yilmaz (Journal of Pediatric Intensive Care, 2020)
Infective endocarditis (IE) is an uncommon infection in children. The recommended treatment for native valve endocarditis secondary to methicillin-susceptible Staphylococcus aureus infection is antistaphylococcal penicillins such as nafcillin or oxacillin. If the initial therapy fails in IE, it can lead to catastrophic results. Nowadays, daptomycin is the best alternative antimicrobial agent to treat children with severe infections, when standard antimicrobial therapy does not yield a result. Herein, in this article, we described a case of a 16-year-old boy who had aortic valve S. aureus endocarditis with septic embolization and stroke. The patient was successfully treated only with daptomycin as well as surgical therapy in the early phase of the infection.
Keywords: infective endocarditis; Staphylococcus aureus; open cardiac surgery; daptomycin; pediatric intensive care unit